Multilayer heat sealing film

By using a composition of high content of linear low density polyethylene and free radical generator in a multilayer film, the problem of thinning of the main layer during the heat sealing process is solved, and the puncture resistance and heat sealing strength of the film are improved, ensuring that Stability and sealing firmness of the packaging process.

CN119325425APending Publication Date: 2025-01-17DOW GLOBAL TECHNOLOGIES LLC
View PDF 30 Cites 0 Cited by

Patent Information

Application Number
CN202380045576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-01
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing multilayer films tend to thin and weaken during the heat sealing process, resulting in the bags prone to cracking and tearing near the seal, and increasing low-density polyethylene to reduce thinning will reduce the processability of the polymer.

Method used

Using a composition containing at least 85% linear low density polyethylene (LLDPE) polymer and free radical generator, the radical generator is essentially decomposed during the extrusion process to increase the complex viscosity ratio of the extruded LLDPE composition. , improve its thinning resistance under heat sealing conditions, while maintaining processability under high shear conditions.

Benefits of technology

It is achieved without reducing the processability of other layers, reducing the thinning of the main layer, improving the puncture resistance and heat sealing strength of the multi-layer film, and ensuring stability and sealing firmness during the packaging process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325425A_ABST
    Figure CN119325425A_ABST
Patent Text Reader

Abstract

Provided herein are multilayer films comprising linear low density polyethylene (LLDPE) and methods of making the same. In some embodiments, the multilayer film comprises: a primary layer comprising an extruded first LLDPE composition; and a second layer comprising a polymer composition. A method for making the multilayer film according to embodiments disclosed herein includes melting a first LLDPE composition and a polymer composition, where the first LLDPE composition includes a first LLDPE polymer and a free radical generator prior to extrusion. The multilayer film may have desirable tear, heat seal, puncture, and dart impact characteristics as a result of being formed from the first LLDPE composition, including the radical generator acting as a rheology modifier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to multilayer polymer films comprising linear low density polyethylene. Background Art

[0002] Polyethylene polymers and copolymers are generally classified into the following groups: High-density polyethylene (HDPE), which typically has a density of about 0.93 g / cm 3 Up to 0.98g / cm 3 Low density polyethylene (LDPE), which usually has a density of about 0.91 g / cm 3 Up to 0.93g / cm 3 and linear low density polyethylene (LLDPE), which typically has a density of about 0.91 g / cm 3 Up to 0.94g / cm 3 The linear low density polyethylene contains short chain branching and less long chain branching than LDPE, and includes substantially linear ethylene polymers further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,155; homogeneously branched linear ethylene polymer compositions, such as those in U.S. Pat. No. 3,645,992; heterogeneously branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698; and / or blends thereof (such as those disclosed in U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,854,045).

[0003] LLDPE is usually coextruded with similar or dissimilar polymers to produce multilayer films. In coextrusion, two or more extruders melt different polymers and feed the polymers into a single extrusion die. The polymers are extruded together to form a film of each polymer containing one or more layers, and these layers are adhered together. The multilayer film may contain a first layer or main layer comprising an LLDPE polymer, which is selected to provide desired physical properties, such as tensile strength, puncture resistance and tear resistance. Other layers in the multilayer film may be selected to provide other desired properties, such as improved heat seal performance, appearance, stiffness, adhesion between layers and / or barriers to the migration of water, oxygen or flavor components.

[0004] Multilayer films are often used in form, fill and seal (FFS) packaging to place goods in a sealed bag made of film. In summary, the FFS packaging process usually includes the following steps:

[0005] 1. The film is unwound from a roll and travels in the machine direction.

[0006] 2. The film is folded so that the outer edges are together, and the edges are welded together using heat and pressure to form a hollow tube with a seam running in the machine direction.

[0007] 3. A set of heated clamps clamp the tube transverse to the longitudinal direction under heat and pressure to form a seal transverse to the longitudinal direction. This forms a bag with an open end in the upstream direction.

[0008] 4. The bag is filled with product from the open end.

[0009] 5. A set of heated clamps clamp the open end of the bag transverse to the machine direction under heat and pressure to form a second seal transverse to the machine direction with the product trapped in the bag between the two seals.

[0010] 6. Cut the closed bag from the end of the tube.

[0011] The forming, filling and sealing system can be vertical (VFFS) or horizontal (HFFS). FFS packaging has strict requirements on the film used to make it. The film must be flexible enough to fold easily to form a bag, but strong enough to withstand the handling and stress in many cases during boxing, transportation, storage and display. The film must be quickly and completely sealed without gaps and voids. The seal must be strong enough to keep the product in the bag before the seal is fully cooled, and the bag closure must remain strong during the whole life of the packaging. The film must provide an effective seal on different equipment with different temperature control capabilities. Ideally, these requirements can be met while making the film as thin as possible to minimize cost, weight and waste generated by the packaging.

[0012] Heat seals can weaken the primary layer of the film in the area adjacent to the seal. When the heated clamps that form the heat seal soften the heat seal layer, they can inadvertently soften the primary layer. The process of moving the film wire and filling the bag puts stress on the heated film. The stress on the heated primary layer causes it to become thinner in the area adjacent to the heat seal. After the film cools and the stress is released, the primary layer remains thin and weak near the seal compared to the rest of the bag. The bag is prone to splitting and tearing near the seal.

[0013] One solution to minimize primary layer thinning is to add 20% or more low-density polyethylene to the LLDPE polymer used for the primary layer. However, LDPE increases the die pressure of the primary layer polymers, reducing their processability.

[0014] It is desirable to reduce thinning in the primary layer without reducing the processability of the polymers in the other layers. Summary of the invention

[0015] One aspect of the present invention is a method of making a multilayer film, the method comprising the steps of: (1) melting (a) a first LLDPE composition and (b) a polymer composition in separate extruders; and (2) coextruding the first LLDPE composition and the polymer composition under conditions suitable for forming a multilayer film, the multilayer film comprising a main layer comprising an extruded LLDPE composition derived from the first LLDPE composition and a second layer comprising the polymer composition, and wherein

[0016] a) prior to extrusion, the first LLDPE composition comprises (i) at least 85 wt% of a first LLDPE polymer, the first LLDPE polymer comprising at least 0.20 vinyl groups per 1000 carbon atoms; and (ii) from 5 parts per million by weight (ppmw) to 1000 parts per million by weight (ppmw).

[0017] 1 million parts by weight of a free radical generator; and

[0018] b) the conditions in the extruder are suitable for substantially decomposing the free radical generator. "Substantially decomposed" means that at least 80% by weight of the free radical generator decomposes under the reaction conditions during extrusion; in some embodiments, at least 90% by weight, or at least 95% by weight, or at least 99% by weight decomposes. In some embodiments, after extrusion is complete, the free radical generator is at an undetectable level. The "primary layer" in a multilayer film may also be referred to as the "first layer."

[0019] A second aspect of the present invention is a multilayer film produced by the method of the first aspect of the present invention.

[0020] A third aspect of the present invention is a multilayer film comprising:

[0021] a) a main layer comprising an extruded first LLDPE composition comprising at least 85 wt% of a first LLDPE polymer, wherein the extruded first LLDPE composition has (1) a complex viscosity ratio (η) of at least 1.7 for complex viscosities measured at 190° C. and at angular frequencies of 0.1 rad / s and 10 rad / s 0.1 / η 10 ); and (2) a ratio of 2.9 to 4.0 (Mz Abs / Mw Abs );as well as

[0022] b) A second layer comprising a polymer composition.

[0023] A fourth aspect of the present invention is a method of using the multilayer film of the second aspect or the third aspect, wherein the multilayer film is used in a form, fill and seal package process.

[0024] A fifth aspect of the present invention is a sealed package produced by the method of the fourth aspect of the present invention.

[0025] Without wishing to be bound by theory, the free radical generator in the first LLDPE composition increases the complex viscosity ratio of the extruded first LLDPE composition by inducing a small increase in long chain branching. The increased complex viscosity ratio means that the extruded first LLDPE composition has a substantially higher viscosity under the low shear conditions present during heat sealing on the FFS line, but does not have a substantially higher viscosity under the high shear conditions present in the extrusion die. The higher viscosity on the FFS line allows the extruded first LLDPE composition to better resist thinning and weakening during the heat sealing process. The lower viscosity in the extrusion die allows the first LLDPE composition to maintain good processability. In addition, in some embodiments, the multilayer films of the present invention have improved puncture resistance and dart drop results. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Depicted are the results of seal strength testing of heat seals made using two inventive films and a comparative example film at a series of elevated temperatures.

[0027] Figure 2 Depicted are the results of hot tack testing of heat seals made using two inventive films and a comparative example film at a series of increasing temperatures. DETAILED DESCRIPTION

[0028] The first LLDPE composition

[0029] The present invention uses a first LLDPE composition comprising a first LLDPE polymer and a free radical generator. In some embodiments, the first LLDPE polymer can be a blend of LLDPE polymers that collectively meet the criteria described herein, and in some embodiments, the first LLDPE polymer is a single LLDPE polymer that meets the criteria described herein. The phrase "first LLDPE polymer" encompasses two embodiments. In some embodiments, the first LLDPE composition also includes other polyethylene polymers, such as a carrier resin used in a masterbatch with a free radical generator, as described below.

[0030] The first LLDPE polymer has a 0.91 g / cm 3 Up to 0.94g / cm 3 Prior to extrusion, it has at least 0.20 vinyl groups per 1000 carbon atoms.

[0031] In some embodiments, the first LLDPE polymer is a copolymer wherein at least 70 weight percent of the polymer is derived from ethylene monomers and at least 2 weight percent of the polymer is derived from one or more comonomers. Examples of suitable comonomers may include α-olefins. Suitable α-olefins may include olefins containing 3 to 20 carbon atoms (C3 to C4). 20 For example, the α-olefin may be C4 to C 20 α-olefins, C4 to C 12 α-olefins, C3 to C 10 In some embodiments, the alpha olefin is selected from the group consisting of propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene and 1-decene. In other embodiments, the alpha olefin is selected from the group consisting of propylene, 1-butene, 1-hexene and 1-octene. In other embodiments, the alpha olefin is selected from the group consisting of propylene, 1-butene, 1-hexene and 1-octene. In other embodiments, the alpha olefin is selected from the group consisting of 1-hexene and 1-octene.

[0032] In some embodiments, repeating units derived from ethylene comprise at least 80 wt%, or at least 90 wt%, or at least 92 wt% of the first LLDPE polymer. In some embodiments, repeating units derived from ethylene comprise up to 98 wt%, or up to 96 wt%, or up to 94 wt%, or up to 93 wt% of the first LLDPE polymer. In some embodiments, repeating units derived from α-olefins comprise up to 20 wt%, or up to 18 wt%, or up to 15 wt%, or up to 12 wt%, or up to 10 wt%, or up to 8 wt% of the first LLDPE polymer. In some embodiments, repeating units derived from α-olefin comonomers comprise at least 2 wt%, or at least 4 wt%, or at least 6 wt%, or at least 7 wt% of the first LLDPE polymer.

[0033] Comonomer content is sometimes expressed as short chain branches per 1000 carbon atoms, where the short chain branches are residues of comonomers and contain no more than 18 carbon atoms, or no more than 10 carbon atoms, or no more than 6 carbon atoms. In some embodiments, the first LLDPE polymer has at least 2, or at least 5, or at least 7, or at least 9 short chain branches per 1000 carbon atoms. In some embodiments, the first LLDPE polymer has at most 20, or at most 18, or at most 15, or at most 13, or at most 11 short chain branches per 1000 carbon atoms.

[0034] In some embodiments, the first LLDPE polymer can be homogeneously branched or heterogeneously branched. The long chain branches contain at least 20 carbon atoms. In some embodiments, the first LLDPE polymer contains no more than 3, or no more than 2, or no more than 1 long chain branches per 1000 carbon atoms. In some embodiments, the first LLDPE polymer is substantially linear except for short chain branches (essentially 0 long chain branches per 1000 carbon atoms) generated by comonomers.

[0035] The first LLDPE polymer has a 0.90 g / cm 3 Up to 0.94g / cm 3 The density of 0.90 g / cm is included and disclosed herein. 3 Up to 0.94g / cm 3 For example, in some embodiments, the density is 0.900 g / cm 3 , 0.905g / cm 3 、0.910g / cm 3 、0.915g / cm 3 , 0.920g / cm 3 , 0.925g / cm 3 , 0.930g / cm 3 or 0.935g / cm 3 The lower limit is 0.940g / cm 3 , 0.935g / cm 3 , 0.930g / cm 3 , 0.925g / cm 3 or 0.920g / cm 3 within the range of the upper limit.

[0036] Prior to coextrusion, the first LLDPE polymer has at least 0.20 vinyl groups per 1000 carbon atoms. All individual values ​​and subranges of at least 0.20 vinyl groups per 1000 carbon atoms are included and disclosed herein. For example, in some embodiments, the first LLDPE polymer has at least 0.20, 0.25, 0.30, or 0.35 vinyl groups per 1000 carbon atoms. In other embodiments, the first LLDPE polymer has up to 1.00 vinyl groups per 1000 carbon atoms, or 0.70 vinyl groups per 1000 carbon atoms, or 0.65 vinyl groups per 1000 carbon atoms, or 0.60 vinyl groups per 1000 carbon atoms, or 0.55 vinyl groups per 1000 carbon atoms, or 0.50 vinyl groups per 1000 carbon atoms, or 0.45 vinyl groups per 1000 carbon atoms.

[0037] In some embodiments, the melt index (I2) of the first LLDPE polymer is in the range of 0.01 g / 10 min to 30 g / 10 min. All individual values ​​and subranges from 0.01 g / 10 min to 30 g / 10 min are included and disclosed herein. For example, in some embodiments, the melt index (I2) is in the range of 0.01, 0.05, 0.1, 0.25, 0.5, 1, 3, 5, 7, 10, 12, 15, 18, 20, 23, or 25 lower limits to 30, 27, 25, 22, 20, 17, 15, 12, 10, 8, 5, 2, 1, 0.9, 0.7, or 0.5 upper limits.

[0038] In some embodiments, the first LLDPE polymer has a weight average molecular weight (Mw) of at least 80,000 Da, or at least 100,000 Da, or at least 120,000 Da prior to extrusion. Abs (All molecular weights are based on absolute molecular weight measurements.) In some embodiments, the first LLDPE polymer has a weight average molecular weight (Mw) of at most 200,000 Da, or at most 160,000 Da, or at most 130,000 Da prior to extrusion. Abs ).

[0039] In some embodiments, the first LLDPE polymer has a molecular weight distribution (Mw) of at least 3, or at least 3.5, or at least 4 prior to extrusion. Abs / Mn Abs ). In some embodiments, the first LLDPE polymer has a molecular weight distribution (Mw / Mn) of at most 6, or at most 5, or at most 4.5 prior to extrusion.

[0040] In some embodiments, prior to extrusion, the Mz of the first LLDPE polymer is Abs / Mw Abs The ratio of Mz to % is at least 2, or at least 2.5, or at least 2.75. In some embodiments, prior to extrusion, the first LLDPE polymer has an Mz of Abs / Mw Abs The ratio is at most 4, or at most 3.5, or at most 3.25, or at most 3, or at most 2.9.

[0041] In some embodiments, prior to extrusion, at a temperature of 190° C. and an angular frequency of 10 rad / s, the first LLDPE polymer has a complex viscosity (η) of no greater than 6000 Pa-s, or no greater than 5000 Pa-s, or no greater than 4900 Pa-s, or no greater than 4800 Pa-s, or no greater than 4700 Pa-s. 10In some embodiments, prior to extrusion, at a temperature of 190° C. and an angular frequency of 10 rad / s, the first LLDPE polymer has a complex viscosity (η 10 ).

[0042] In some embodiments, prior to extrusion, at a temperature of 190° C. and an angular frequency of 0.1 rad / s, the first LLDPE polymer has a complex viscosity (η) of no greater than 9000 Pa-s, or no greater than 8000 Pa-s, or no greater than 7800 Pa-s, or no greater than 7600 Pa-s. 0.1 In some embodiments, prior to extrusion, at a temperature of 190° C. and an angular frequency of 0.1 rad / s, the first LLDPE polymer has a complex viscosity (η 0.1 ).

[0043] Polyethylene polymers are characterized by a complex viscosity ratio (η 0.1 / η 10 ), which is the ratio of the complex viscosities measured at angular frequencies of 0.1 rad / s and 10 rad / s and a temperature of 190° C. In some embodiments, prior to extrusion, the first LLDPE polymer has a complex viscosity ratio (η) of no greater than 2.5, or no greater than 2.25, or no greater than 2, or no greater than 1.9, or no greater than 1.8, or no greater than 1.75, or no greater than 1.7. 0.1 / η 10 In some embodiments, the first LLDPE polymer has a complex viscosity ratio (η) of at least 1.5. 0.1 / η 10 ).

[0044] Examples of suitable LLDPE polymers commercially available from The Dow Chemical Company include those sold under the trademark DOWLEX TM TG2085B、DOWLEX TM GM8051、ELITE TM 5401G、ELITE TM NG5401B、ELITE TM XB 81844.38 and ELITE TM A polymer sold as AT 6501.

[0045] The first LLDPE polymer can be produced via a gas phase, solution phase or slurry polymerization process or any combination thereof, using any type of reactor or reactor configuration known in the art (e.g., a fluidized bed gas phase reactor, a loop reactor, a stirred tank reactor, a batch reactor and / or any combination thereof in parallel, in series). In some embodiments, a gas phase or slurry phase reactor is used. A suitable first LLDPE polymer can be produced according to the method described on pages 15 to 17 and pages 20 to 22 in WO 2005 / 111291 A1. The catalyst for preparing the first LLDPE polymer described herein may include a Ziegler-Natta catalyst, a chromium catalyst, a metallocene catalyst, a constrained geometry catalyst or a single site catalyst. In some embodiments, the first polyethylene polymer may be a unimodal LLDPE prepared using a single-stage polymerization (e.g., a slurry, solution or gas phase polymerization). In other embodiments, the first LLDPE polymer may be a unimodal LLDPE prepared in a loop reactor, such as in a single-stage loop polymerization process. The loop reactor process is further described in WO / 2006 / 045501 or WO2008104371. Multimodal (e.g. bimodal) polymers may be produced by mechanical blending of two or more separately prepared polymer components or in situ in a multistage polymerization process (or both). In some embodiments, the first LLDPE polymer may be a multimodal LLDPE prepared in situ in a multistage (i.e. two or more stages) polymerization, or a multimodal LLDPE prepared in a one-stage polymerization by using one or more different polymerization catalysts (including single-site catalysts, multisite catalysts or dual-site catalysts). For example, the first LLDPE polymer may be a multimodal LLDPE produced in at least two stages of polymerization using the same catalyst (e.g. a single-site catalyst or a Ziegler-Natta catalyst), as disclosed in U.S. Pat. No. 8,372,931. Thus, for example, two solution reactors, two slurry reactors, two gas phase reactors, or any combination thereof, in any order may be utilized, as disclosed in U.S. Pat. Nos. 4,352,915 (two slurry reactors), 5,925,448 (two fluidized bed reactors), and 6,445,642 (loop reactor followed by a gas phase reactor). However, in other embodiments, the first LLDPE polymer may be a multimodal polymer, for example, LLDPE, produced using slurry polymerization in a loop reactor followed by gas phase polymerization in a gas phase reactor, as disclosed in EP 2653392 A1.

[0046] Before the first LLDPE composition is coextruded, it also includes a free radical generator. Examples of free radical generators include organic peroxides and organic azo compounds. In some embodiments, the free radical generator is an organic peroxide compound.

[0047] In some embodiments, the free radical generator has a half-life of no greater than 200 seconds at 220° C. For example, some embodiments of the free radical generator may have a half-life of no greater than 175 seconds, 150 seconds, or 125 seconds at 220° C. Some embodiments of the free radical generator may have a half-life of at least 30 seconds, or at least 45 seconds, or at least 60 seconds at 220° C.

[0048] In some embodiments, the free radical generator may have a molecular weight of 200 Daltons to 1000 Daltons (Da). All individual values ​​and subranges of 200 Daltons to 1000 Daltons are included and disclosed herein. For example, in some embodiments, the free radical generator may have a molecular weight of at least 225 Da or 250 Da. In some embodiments, the free radical generator may have a molecular weight of at most 1000 Da, or at most 700 Da.

[0049] In some embodiments, the free radical generator can be a cyclic peroxide. Examples of suitable cyclic peroxides can be represented by the following formula:

[0050]

[0051] wherein R1-R6 are independently hydrogen or an inert substituted or unsubstituted C1 to C 20 Alkyl, C3 to C 20 Cycloalkyl, C6 to C 20 Aryl, C7 to C 20 Arylalkyl or C7 to C 20 Representative of the inert substituents contained in R1 to R6 are hydroxyl, C1 to C 20 Alkoxy, linear or branched C1 to C 20 Alkyl, C6 to C 20 In some embodiments, R1 to R6 are each independently a lower alkyl group, including, for example, C1 to C 10 Alkyl or C1 to C4 alkyl.

[0052] Some of the cyclic peroxides described herein are commercially available, but others can be made by contacting a ketone with hydrogen peroxide, as described in: USP 3,003,000; Uhlmann, 3rd edition, Vol. 13, pp. 256-57 (1962); the article “Studies in Organic Peroxides XXV Preparation, Separation and Identification of Peroxides Derived from Methyl Ethyl Ketone and Hydrogen Peroxide”, Milas, N. A. and Golubovic, A., Journal of the American Chemical Society (J. Am. Chem. Soc), Vol. 81, pp. 5824-26 (1959); Organic Peroxides. Peroxides, Swern, D., ed., Wiley-Interscience, New York (1970); and Houben-Weyl, Methoden der Organische Chemie, El 3, Vol. 1, p. 736.

[0053] In some embodiments, the cyclic peroxide may be 3,6,9-triethyl-3-6-9-trimethyl-1,4,7-triperoxynonane, which is commercially available from AkzoNobel under the trade name TRIGONOX 301. The cyclic peroxide used herein may be a liquid, solid, or paste, depending on the melting point of the peroxide and the diluent, if any, in which the peroxide is carried.

[0054] The free radical generator should be present in an amount suitable for increasing the low shear viscosity of the first LLDPE composition. In some embodiments, the ratio of the free radical generator to the first LLDPE composition is from 5 ppmw to 1000 ppmw. All individual values ​​and subranges from 5 ppmw to 1000 ppmw are included herein and disclosed herein; for example, the ratio of the free radical generator to the first LLDPE composition may be in the range of 5 ppmw, 10 ppmw, 20 ppmw, 30 ppmw, 40 ppmw, or 50 ppmw to an upper limit of 40 ppmw, 50 ppmw, 60 ppmw, 65 ppmw, 75 ppmw, 100 ppmw, 150 ppmw, 250 ppmw, 350 ppmw, 450 ppmw, 550 ppmw, 650 ppmw, 750 ppmw, 850 ppmw, 950 ppmw, or 1000 ppmw. In some embodiments, the weight ratio of the free radical generator to the first LLDPE composition, relative to the total amount of polymer, can be in the range of 5 ppmw to 100 ppmw, or 5 ppmw to 75 ppmw, or 10 ppmw to 75 ppmw, or 5 ppmw to 50 ppmw, or 10 ppmw to 50 ppmw, or 15 ppmw to 35 ppmw, or 20 ppmw to 40 ppmw.

[0055] In some embodiments, the first LLDPE composition optionally comprises other polyethylene polymers. In some embodiments, any other polymer is a LLDPE polymer. In some embodiments, the other polymer is a low density polyethylene.

[0056] The first LLDPE polymer comprises at least 85 wt % of the first LLDPE composition. In some embodiments, the first LLDPE polymer comprises at least 90 wt %, or at least 95 wt %, or at least 99 wt % of the first LLDPE composition. In some embodiments, the LDPE polymer may comprise at least 1 wt %, or at least 2 wt %, or at least 3 wt % of the first LLDPE composition. In some embodiments, the LDPE polymer comprises 0 wt % to 15 wt %, or 0 wt % to 10 wt %, or 0 wt % to 5 wt %, or 0 wt % to 3 wt %, or 0 wt % to 1 wt %, or substantially 0 wt % of the first LLDPE composition.

[0057] One way in which other polymers can be introduced into the first LLDPE composition is to blend the free radical generator with the carrier polymer to form a masterbatch, as described in PCT Patent Publication 2017 / 172273A1. The masterbatch can be blended with the first LLDPE polymer to form the first LLDPE composition and the free radical generator is dispersed throughout the first LLDPE polymer. The masterbatch provides better control and better dispersion of the free radical generator concentration.

[0058] The carrier polymer can be a low density polyethylene (LDPE), a linear low density polyethylene (LLDPE), a medium density polyethylene (MDPE), a high density polyethylene (HDPE), or a combination thereof. In some embodiments, the carrier polymer is a LLDPE polymer. When the carrier polymer is a LLDPE polymer, it can have the same description, embodiments, and examples listed for the first LLDPE polymer, except that the presence of vinyl end groups is optional and not required. In some embodiments, the carrier polymer is a LDPE polymer.

[0059] In some embodiments, the masterbatch composition comprises at least 100 ppmw, or at least 200 ppmw, or at least 300 ppmw, or at least 400 ppmw, or at least 500 ppmw of free radical generator. In some embodiments, the masterbatch composition comprises at most 4000 ppmw, or at most 3000 ppmw, or at most 2000 ppmw, or at most 1500 ppmw, or at most 1000 ppmw of free radical generator.

[0060] Depending on the concentration of the free radical generator in the masterbatch composition, the first LLDPE polymer and the masterbatch can be blended in a ratio of 60:40 to 99.9:0.1. All individual values ​​and subranges are included and disclosed herein. For example, in some embodiments, the first LLDPE polymer and the masterbatch can be blended in a ratio of 65:35 to 99.9:0.1, 65:35 to 99.9:0.1, 70:30 to 99.9:0.1, 75:25 to 99.9:0.1, 80:20 to 99.9:0.1, 85:15 to 99.9:0.1, 90:10 to 99.9:0.1, 95:5 to 99.9:0.1, 97:3 to 99.9:0.1, 95:5 to 99:1, or 97:3 to 99:1. The first LLDPE polymer and the masterbatch may also be blended such that the amount of the masterbatch in the first LLDPE composition is in the range of 0.1 wt % to 40 wt %. All individual values ​​and subranges are included and disclosed herein. For example, in some embodiments, the first LLDPE polymer and the masterbatch may be blended such that the amount of the masterbatch in the first LLDPE composition is at least 0.1 wt %, or at least 0.2 wt %, or at least 0.5 wt %, or at least 1 wt %, or at least 2 wt %, and in some embodiments, the first LLDPE polymer and the masterbatch may be blended such that the amount of the masterbatch in the first LLDPE composition is no greater than 15 wt %, or no greater than 10 wt %, or no greater than 5 wt %, or no greater than 3 wt %.

[0061] In some embodiments, the first LLDPE composition may contain other additives commonly used in LLDPE films, such as plasticizers, flame retardants, antioxidants, acid scavengers, light and heat stabilizers, lubricants, pigments, antistatic agents, slip agents, and heat stabilizers. In some embodiments, the other additives account for no more than 5 wt%, or no more than 4 wt%, or no more than 3 wt%, or no more than 2 wt%, or no more than 1 wt% of the first LLDPE composition. In some embodiments, the other additives account for essentially 0 wt% of the first LLDPE composition.

[0062] In some embodiments herein, the first LLDPE composition comprises no greater than 2,000 ppmw of a primary antioxidant. All individual values ​​and subranges of 0 ppmw to 2,000 ppmw of a primary antioxidant are included and disclosed herein. For example, in some embodiments, the first LLDPE composition may comprise from the lower limit of 0 ppmw, 10 ppmw, 25 ppmw, 50 ppmw, 100 ppmw, 200 ppmw, 300 ppmw, 400 ppmw, 500 ppmw, 600 ppmw, 700 ppmw, 800 ppmw, 900 ppmw, 1000 ppmw, 1100 ppmw, 1200 ppmw, 1300 ppmw, 1400 ppmw, 1500 ppmw, 1600 ppmw, 1700 ppmw, 1800 ppmw, or 1900 ppmw to 15 ppmw, 3 In some embodiments, the first LLDPE composition may contain up to 250 ppmw, up to 200 ppmw, up to 150 ppmw, up to 100 ppmw, up to 50 ppmw, up to 25 ppmw, or 0 ppmw of primary antioxidant. In other embodiments, the first LLDPE composition may include 10 ppmw to 1000 ppmw, 10 ppmw to 500 ppmw, 500 ppmw to 1000 ppmw, 10 ppmw to 300 ppmw, or 20 ppmw to 100 ppmw of a primary antioxidant. Primary antioxidants are free radical scavengers, which are typically organic molecules composed of hindered phenols or hindered amine derivatives. Examples of primary antioxidants include those well known in the polyolefin industry, such as those available from BASF under the name IRGANOX®. TM 1010 Commercially available pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenol)propionate) or available from BASF under the name IRGANOX TMOctadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is commercially available from 1076. Secondary antioxidants decompose hydroperoxides and are typically organic molecules composed of phosphites, phosphonites, or thio compounds. Exemplary secondary antioxidants include tris(2,4-di-tert-butylphenyl) phosphite (which is available from BASF under the name IRGAFOS TM 168 commercially available) or tris(nonylphenyl) phosphite.

[0063] Other polymer layer materials

[0064] In some embodiments, the first LLDPE composition is coextruded with the polymer composition to form a multilayer film comprising a main layer derived from the first LLDPE composition and a second layer derived from the polymer composition. The two layers are directly or indirectly adhered to each other.

[0065] The choice of polymer composition depends on the purpose of the layer it will form. Common layers in multilayer LLDPE films include heat seal layers, print layers, stiffness layers, barrier layers and tie layers.

[0066] The polymer used for the heat seal layer is generally a thermoplastic polymer that can easily melt and adhere under heat seal conditions during forming, filling and sealing the package. These are generally referred to as heat seal polymers by those skilled in the art. Examples of common heat seal polymers include LLDPE (made using Ziegler-Natta catalysts or metallocene catalysts), ethylene-vinyl acetate copolymers and polymer blends thereof. In many embodiments, the heat seal polymer contains metallocene LLDPE.

[0067] In some embodiments, the heat seal polymer has a thermal conductivity of at least 0.90 g / cm 3 , or at least 0.91g / cm 3 In some embodiments, the heat seal polymer has an average density of at most 0.94 g / cm 3 , or up to 0.93g / cm 3 , or up to 0.92g / cm 3 The average density of .

[0068] In some embodiments, the heat seal polymer has a melt index (I2) of at least 0.2 g / 10 min, or at least 0.5 g / 10 min, or at least 0.7 g / 10 min, or at least 1 g / 10 min, or at least 2 g / 10 min. In some embodiments, the heat seal polymer has a melt index (I2) of at most 10 g / 10 min, or at most 5 g / 10 min, or at most 3 g / 10 min.

[0069] In some embodiments, the heat seal polymer has a melting temperature of at least 80°C, or at least 85°C, or at least 90°C, or at least 100°C. In some embodiments, the heat seal polymer has a melting temperature of at most 130°C, or at most 125°C, or at most 120°C.

[0070] In some embodiments, the heat seal polymer has a seal initiation temperature (for a seal strength of 4N / 15mm) of at least 80°C, or at least 85°C, or at least 90°C, or at least 95°C. In some embodiments, the heat seal polymer has a seal initiation temperature (for a seal strength of 4N / 15mm) of at most 130°C, or at most 120°C, or at most 110°C, or at most 105°C.

[0071] In some cases, the Ziegler-Natta polyethylene may have a higher density and a seal initiation temperature and a lower melt index within the above ranges, while the metallocene polyethylene may have a lower density and a seal initiation temperature and a higher melt index within the above ranges.

[0072] In some embodiments, the heat seal polymer has a hot tack strength of at least 0.6 N / 15 mm, or at least 0.8 N / 15 mm, or at least 1 N / 15 mm, or at least 1.5 N / 15 mm at 110° C. There is no maximum desired hot tack strength, but in some embodiments, a hot tack strength above 10 N / 15 mm or 5 N / 15 mm at 110° C. is not necessary.

[0073] Examples of suitable heat seal polymers include ELITE TM Reinforced polyethylene polymers are commercially available under the tradename DOWLEX TM Certain LLDPE polymers are commercially available under the trademark TEFLON(R).

[0074] The print layer is typically located on the surface of the multilayer film, opposite the heat seal layer. The polymer can be selected to have a good appearance, such as high gloss, and to provide a good surface for ink adhesion. Examples of common polymers in the print layer include LLDPE derived from Ziegler-Natta or metallocene catalysts. Common print layer polymers can be found under the trademark DOWLEX TM GM 8051、DOWLEX TM TG2085B、DOWLEX TM GM8070、DOWLEX TM 2049, ELITE TM AT 6501 and INNATE TM ST50 was purchased commercially.

[0075] The barrier layer can reduce the migration of gases, moisture and / or flavor elements through the multilayer film. Examples of common barrier polymers include ethylene vinyl alcohol, ethylene vinyl acetate, polyvinylidene chloride, polypropylene, polyamide, polyethylene terephthalate, and polyvinyl chloride. Polymers for barrier layers are commercially available, such as those sold under the trademark SARAN TM , Eval, Ube nylon-6 and Miramid.

[0076] Tie layers can improve the adhesion of different layers in a multilayer film, especially when the different layers contain incompatible polymers. Examples of common tie layer polymers include ethylene acrylic acid copolymers and ethylene vinyl acetate copolymers. Examples of common tie layers can be found under the trademark BYNEL TM , Plexar, EMAC, Surpass and Novapol are commercially available.

[0077] Coextrusion and multilayer films :

[0078] The above materials can be coextruded to form a multilayer film by known methods. The materials can be melted in a separate extruder. The molten material is fed to an extrusion die. The die is designed to extrude each material into one or more discrete layers and continuous layers in a multilayer film.

[0079] In cast film extrusion, the die is a slot die and the film is extruded onto a chilled roll, quenched and wound onto a roll.

[0080] In blown film extrusion, the die is a circular die. Bubbles (such as air or nitrogen) are trapped in the circular film between the die and a pair of downstream pressure rollers. The film passes through the air bubbles and is biaxially stretched before it solidifies. The film is cooled, flattened and wound into a roll.

[0081] Examples of coextrusion processes are described in LyondellBasell, A Guide to Polyolefin Film Extrusion, publication 6047 / 1004 (available from lyb.com); LyondellBasell, How to Solve Blown Film Problems, publication 6483 / 0559 (available from www.lyondellbasell.com); Qenos Pty, Ltd., Film Extrusion and Conversion–Technical Guide (July 2015) (available from qenos.com); Golghate et al., Adopting Best Practices in Blown Film Extrusion Process: Need of the Hour to Control Environmental Burdens, 3(1), International Journal of Industrial Engineering and Technology Journal of Industrial Engineering Technology)》 , 63-80 (2013); and Goff et al., Dynisco The Dynisco Extrusion Processors Handbook, 2nd Edition (Available from www.dynisco.com ).

[0082] In the process of the present invention, the conditions in the extruder (including the extrusion die) for the first LLDPE composition should be suitable for substantially decomposing the free radical generator. The necessary conditions may depend on the selected free radical generator and the effectiveness of mixing in the extruder. In some embodiments, the first LLDPE composition obtains a temperature of at least 180°C, or at least 190°C, or at least 200°C, or at least 210°C, or at least 215°C. Generally, the temperature is low enough so that the first LLDPE composition is not substantially degraded. In some embodiments, the temperature does not exceed 250°C, or 240°C, or 230°C. In some embodiments, the first LLDPE composition maintains the selected temperature for at least 30 seconds, or at least 45 seconds, or at least 60 seconds, and in some embodiments, the first LLDPE composition maintains the selected temperature for no more than 15 minutes, or no more than 10 minutes, or no more than 5 minutes, or no more than 3 minutes, or no more than 2 minutes. Suitable conditions for decomposing free radical generators are typically achieved in extruders used for conventional multilayer film extrusion, so in some embodiments, no changes to existing procedures are required.

[0083] The product of the coextrusion process is a multilayer film. It includes at least (1) a primary layer derived from a first LLDPE composition and (2) a second layer derived from a polymer composition and directly and indirectly adhered to the primary layer. In some embodiments, the second layer is a heat seal layer containing a heat seal polymer as described above. The heat seal layer (if present) generally forms one surface of the multilayer film.

[0084] In some embodiments, the multilayer film further comprises (3) a third polymer layer, which is directly or indirectly adhered to the main layer on the side opposite to the second layer. For example, the multilayer film may include at least 3 layers, which include (1) a main layer, (2) a heat seal layer, which is directly and indirectly adhered to one side of the main layer, forming one surface of the multilayer film; and (3) another surface layer, which is directly and indirectly adhered to the main layer on the side opposite to the heat seal layer forming the other surface of the multilayer film. In some embodiments, the other surface layer is a printing layer as described above.

[0085] In structures of three or more layers, the primary layer is often an inner layer rather than a surface layer, and is often referred to as the "core" layer.

[0086] In some embodiments, the multilayer film includes multiple layers, such as 5, 6, 7, 8 or 9 layers. For example, in addition to the aforementioned 3 layers, the multilayer film may also contain a barrier layer and one or more tie layers to promote adhesion between the barrier layer and the surrounding layers. In some embodiments, the barrier layer and the tie layer are inner layers, rather than surface layers.

[0087] In some embodiments, the multilayer film has a thickness of at least 10 μm, or at least 20 μm, or at least 30 μm. In some embodiments, the multilayer film has a thickness of at most 200 μm, or at most 150 μm, or at most 120 μm, or at most 100 μm.

[0088] In some embodiments, the main layer accounts for at least 30%, or at least 40%, or at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90% of the thickness of the multilayer film. In some embodiments, the layers other than the main layer account for at least 5%, or at least 10%, or at least 20%, or at least 30% of the thickness of the multilayer film. In some embodiments, the second layer accounts for at least 5%, or at least 10%, or at least 20% of the thickness of the multilayer film. In some embodiments, the third layer accounts for at least 5%, or at least 10%, or at least 20% of the thickness of the multilayer film.

[0089] Decomposition of the free radical generator during extrusion can change the properties of the first LLDPE composition in the main layer. Without wishing to be bound by theory, we hypothesize that this change is caused by a small amount of long chain branching introduced by the free radical generator. The resulting first LLDPE composition can be referred to as an extruded first LLDPE composition.

[0090] In some embodiments, the extruded first LLDPE composition has a weight average molecular weight (Mw) of at least 90,000 Da, or at least 110,000 Da, or at least 122,000 Da, or at least 125,000 Da, or at least 130,000 Da. AbsIn some embodiments, the extruded first LLDPE composition has a weight average molecular weight (Mw) of at most 200,000 Da, or at most 160,000 Da. Abs ).

[0091] In some embodiments, the extruded first LLDPE composition has a molecular weight distribution (Mw Abs / Mn Abs In some embodiments, the extruded first LLDPE composition has a molecular weight distribution (Mw Abs / Mn Abs ).

[0092] In some embodiments, the Mz of the extruded first LLDPE composition is Abs / Mw Abs The ratio of Mz to Mg is at least 2.5, or at least 2.9, or at least 3.1, or at least 3.2. In some embodiments, the Mz of the extruded first LLDPE composition is Abs / Mw Abs The ratio is at most 5.0, or at most 4.0, or at most 3.5.

[0093] In some embodiments, the Mz of the extruded first LLDPE composition is Abs / Mw Abs In some embodiments, the extruded first LLDPE composition has a Mz / Mw ratio that is at least 5%, or at least 8%, or at least 10%, or at least 12%, or at least 15%, or at least 17% higher than the Mz / Mw of the first LLDPE polymer before extrusion. In some embodiments, the extruded first LLDPE composition has a Mz / Mw ratio that is at most 30%, or at most 25%, or at most 20% higher than the Mz / Mw of the first LLDPE polymer before extrusion.

[0094] In some embodiments, at a temperature of 190° C. and an angular frequency of 10 rad / s, the extruded first LLDPE composition has a complex viscosity (η) of no greater than 6000 Pa-s, or no greater than 5000 Pa-s, or no greater than 4900 Pa-s, or no greater than 4800 Pa-s, or no greater than 4700 Pa-s. 10 In some embodiments, at a temperature of 190° C. and an angular frequency of 10 rad / s, the extruded first LLDPE composition has a complex viscosity (η 10 ).

[0095] In some embodiments, at a temperature of 190° C. and an angular frequency of 0.1 rad / s, the extruded first LLDPE composition has a complex viscosity (η) of at least 7000 Pa-s, or at least 8000 Pa-s, or at least 9000 Pa-s, or at least 10000 Pa-s. 0.1 In some embodiments, at a temperature of 190° C. and an angular frequency of 0.1 rad / s, the extruded first LLDPE composition has a complex viscosity (η) of not more than 15,000 Pa-s, or not more than 12,000 Pa-s, or not more than 11,000 Pa-s. 0.1 ).

[0096] In some embodiments, the extruded first LLDPE composition has a complex viscosity ratio (η) of at least 1.6, or at least 1.7, or greater than 1.7, or at least 1.75, or at least 1.8, or at least 1.85, or at least 1.9, or at least 1.95. 0.1 / η 10 In some embodiments, the extruded first LLDPE composition has a complex viscosity ratio (η) of no greater than 4, or no greater than 3, or no greater than 2.5. 0.1 / η 10 ).

[0097] In some embodiments, the complex viscosity (η) of the extruded first LLDPE composition is 0.1 ) (at a temperature of 190° C. and an angular frequency of 0.1 rad / s) is at least 5% higher, or at least 10% higher, or at least 15% higher, or at least 20% higher, or at least 25% higher, or at least 30% higher, or at least 35% higher, or at least 40% higher than the complex viscosity of the first LLDPE polymer before extrusion. In some embodiments, the complex viscosity (η) of the extruded first LLDPE composition is at least 5% higher, or at least 10% higher, or at least 15% higher, or at least 20% higher, or at least 25% higher, or at least 30% higher, or at least 35% higher, or at least 40% higher. 0.1 ) (at a temperature of 190° C. and an angular frequency of 0.1 rad / s) is up to 100% higher, or up to 60% higher, than the complex viscosity of the first LLDPE polymer before extrusion.

[0098] In some embodiments, the complex viscosity ratio (η 0.1 / η 10 ) is at least 5%, or at least 10%, or at least 15%, or at least 20% higher than the complex viscosity ratio of the first LLDPE polymer before extrusion. There is no maximum desired increase in complex viscosity ratio, but in some embodiments, an increase of more than 50% is not necessary.

[0099] In some embodiments, the multilayer films of the present invention have a secant modulus of at least 140 MPa, or at least 150 MPa, or at least 160 MPa, or at least 170 MPa at 2%. In some embodiments, the multilayer films of the present invention have a secant modulus of at most 250 MPa, or at most 200 MPa, or at most 180 MPa at 2%.

[0100] In some embodiments, the multilayer films of the present invention have a puncture force of at least 1.5 N / μm film thickness, or at least 1.55 N / μm film thickness, or at least 1.60 N / μm film thickness, or at least 1.65 N / μm film thickness. In some embodiments, the multilayer films of the present invention have a puncture force of at most 5 N / μm, or at most 3 N / μm. In some embodiments, the puncture force of the multilayer films of the present invention is at least 5% higher, or at least 10% higher, or at least 12% higher than the puncture force of a comparable film in which the primary layer contains a comparable polymer extruded without a free radical generator.

[0101] In some embodiments, the multilayer films of the present invention have a dart impact resistance of at least 5 g / μm film thickness, or at least 6 g / μm film thickness, or at least 6.2 g / μm film thickness, or at least 6.5 g / μm film thickness, or at least 7 g / μm film thickness, or at least 7.5 g / μm film thickness. In some embodiments, the multilayer films of the present invention have a dart impact resistance of at most 20 g / μm, or at most 10 g / μm. In some embodiments, the dart impact resistance of the multilayer films of the present invention is at least 5% higher, or at least 10% higher, or at least 15% higher, or at least 20% higher, or at least 25% higher than the dart impact resistance of a comparable film in which the primary layer contains a comparable polymer extruded without a free radical generator.

[0102] In some embodiments, the multilayer films of the present invention have a haze of at most 25%, or at most 22%, or at most 20%, or at most 18%. There is no minimum desired haze level (0%), but in many embodiments, a haze below 10% is not necessary.

[0103] Application of multilayer films

[0104] The multilayer films of the present invention can be used in conventional forming, filling and sealing methods, such as vertical forming, filling and sealing (VFFS) methods or horizontal forming, filling and sealing (HFFS) methods. Examples of suitable methods are described in U.S. Patents 4,757,668; 4,807,420; 5,279,098; 5,540,035 and 5,533,322 and the publication "Vertical Form Fill and Seal", published by Rockwell Automation Inc. and available from their website www.rockwellautomation.com Suitable equipment is commercially available.

[0105] Compared with similar packages containing unextruded polymers, the multilayer films of the present invention with an extruded main layer can have improved packaging properties. In some embodiments, the modification substantially increases the bag drop strength (bag drop strength) of the packaging manufactured using the multilayer film. In some embodiments, the modification substantially increases the strength of the heat seal manufactured using the multilayer film at high temperatures. In some embodiments, when sealing and testing as described in the "Test Methods", the film can provide a seal strength within 10% (or 5%) of the maximum strength over a range of 5°C, or 10°C, or 15°C, or 20°C. A wide range of effective sealing temperatures is valuable because a single film can provide a secure seal on a variety of equipment operating at different temperatures.

[0106] The present invention is further illustrated by the following examples, which illustrate specific embodiments of the invention but do not limit the broad scope of the invention.

[0107] Example

[0108] Test Method

[0109] The parameters described in this application can be determined using the following measurements:

[0110]

[0111] Molecular weight

[0112] Molecular weight / molecular weight distribution and Mark-Houwink plots for branching structure analysis were measured using triple detector gel permeation chromatography. The methods and equations used are described in U.S. Pat. No. 8,871,887. U.S. Pat. No. 8,871,887 is incorporated by reference. For gel permeation chromatography (GPC) methods (conventional GPC, light scattering (LS) GPC, viscometry GPC, and gpcBR), a triple detector gel permeation chromatography (3D-GPC or TDGPC) system was used. The system includes a Robotic Assistant Delivery (RAD) high temperature GPC system [other suitable high temperature GPC instruments include Waters, Milford, Mass. Model 150C High Temperature Chromatograph; Polymer Laboratories, Shropshire, UK Model 210 and Model 220; and Polymer Char GPC-IR (Valencia, Spain)] equipped with a Precision Detectors (Amherst, Mass.) 2-angle laser light scattering (LS) detector Model 2040, an IR4 infrared detector from Polymer ChAR (Valencia, Spain), and a 4-capillary solution viscometer (DP) (other suitable viscometers include Viscotek (Houston, Tex.) 150R 4-capillary solution viscometer (DP)). A GPC with these latter two independent detectors and at least one of the former detectors may be referred to as "3D-GPC" or "TDGPC", while the term "GPC" alone usually refers to conventional GPC. Data collection is performed using software such as PolymerChar GPC-IR. The system is also equipped with an online solvent degasser from Polymer Labs.

[0113] The eluent from the GPC column set flows through each detector arranged in series in the following order: LS detector, IR4 detector, followed by DP detector. The systematic method for determining the multi-detector offset is carried out in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatography Polym., Chapter 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym., Chapter 13, (1992)). Olexis LS columns are used. The sample transport chamber is operated at 140°C and the column chamber is operated at 150°C. The sample is prepared at a concentration of 0.1 grams of polymer in 50 milliliters of solvent. The chromatographic solvent and sample preparation solvent are 1,2,4-trichlorobenzene (TCB) containing 200 ppmw of 2,6-di-tert-butyl-4-methylphenol (BHT). The solvent is purged with nitrogen. The polymer sample is gently stirred at 160°C for four hours. The injection volume was 200 μL. The flow rate through the GPC was set at 1 mL / min.

[0114] For conventional GPC, an IR4 detector is used, and the GPC column set is calibrated by running 21 narrow molecular weight distribution polystyrene standards. The molecular weight of the standards ranges from 580 g / mol to 8,400,000 g / mol, and the standards are contained in six "mixed liquid" mixtures. Each standard mixture is at least ten steps apart between individual molecular weights. Polystyrene standards are prepared under the following conditions: for molecular weights equal to or greater than 1,000,000 g / mol, they are prepared as "0.025 g in 50 mL of solvent", and for molecular weights less than 1,000,000 g / mol, they are prepared as "0.05 g in 50 mL of solvent". The polystyrene standards are dissolved at 80 ° C by gentle stirring for 30 minutes. The number average molecular weight, weight average molecular weight, and z average molecular weight are calculated by the following equations, for example as described in U.S. Patent No. 8,871,887.

[0115] For LS GPC, a precision detector PDI2040 detector model 2040 is used. For 3D-GPC, the absolute weight average molecular weight is calculated by the equation, for example, as described in U.S. Patent No. 8,871,887. The gpcBR branching index is determined by calibrating the light scattering, viscosity and concentration detectors and subtracting the baseline. The integration window is set for the integration of the low molecular weight retention volume range in the light scattering and viscometer chromatograms, which indicate the presence of detectable polymers from the refractive index chromatogram. Linear polyethylene standards are used to establish polyethylene and polystyrene Mark-Houwink constants. Constants are used to construct two linear references, conventional calibrations of polyethylene molecular weight and polyethylene intrinsic viscosity as a function of elution volume, for example, as described in U.S. Patent No. 8,871,887. In order to determine the gpcBR branching index, the light scattering elution area of ​​the sample polymer is used to determine the molecular weight of the sample. The final Mark-Houwink constant is used for analysis, for example, as described in U.S. Patent No. 8,871,887.

[0116] Vinyl Unsaturation

[0117] The sample was prepared by adding 130 mg of sample to 3.25 g of 50 / 50 (by weight) tetrachloroethane-d2 / perchloroethylene with 0.001 M Cr(AcAc)3 in a Norell 1001-7 10 mm NMR tube. The sample was purged by bubbling nitrogen through the solvent for about 5 minutes via a pipette inserted into the tube, capped, sealed with Teflon tape, and then soaked overnight at room temperature to promote sample dissolution. The sample was heated and vortexed at 115°C to ensure homogeneity.

[0118] 1H NMR was performed on a Bruker AVANCE 400MHz spectrometer equipped with a Bruker dual DUL high temperature probe (CryoProbe) and at a sample temperature of 120°C. Two experiments were run to obtain a spectrum, a control spectrum for quantitative total polymer protons, and a double presaturation experiment, which suppresses strong polymer backbone peaks and enables a high sensitivity spectrum for quantitative end groups. The control was run with a ZG pulse, 4 scans, AQ 1.64s, D1 (relaxation delay) 14s. The double presaturation experiment was run with a modified pulse sequence, 100 scans, DS 4, AQ 1.64s, D1 (presaturation time) 1s, D13 (relaxation delay) 13s. The region between 4.95ppmw and 5.15ppmw was integrated to determine the vinyl content.

[0119] Polymer viscosity

[0120] The samples were compression molded at 190°C under 25,000 pounds of pressure in air for 6.5 minutes, and the plaques were then allowed to cool on a laboratory bench. The thickness of the plaques was ~3 mm. Constant temperature frequency sweep measurements were performed on an ARES strain controlled parallel plate rheometer (TA Instruments) equipped with 25 mm parallel plates under a nitrogen purge. For each measurement, the rheometer was thermally equilibrated for at least 30 minutes before the gap was zeroed. The sample was placed on the plate and allowed to melt at 190°C for five minutes. The plates were then closed to 2 mm, the sample trimmed, and the test was then started. An additional five minute delay was built into the method to allow temperature equilibration. The experiments were performed at 190°C over a frequency range of 0.1 rad / s-100 rad / s at five points per decade. The strain amplitude was constant at 10%. The stress response was analyzed in terms of amplitude and phase, from which the storage modulus (G'), loss modulus (G"), complex modulus (G*), dynamic complex viscosity (η*), and tan (δ) or loss tangent values ​​were calculated.

[0121] Masterbatch :

[0122] A masterbatch (MB-1) was prepared containing DOW TM 1000ppmw of Trigonox 301 free radical generator in LDPE 4016. Masterbatch was produced on a ZSK-26mm Coperian co-rotating twin screw extruder (TSE) under a nitrogen atmosphere. The extruder was an 11 barrel, 44L / D electrically heated and water-cooled machine with a maximum RPM of 1200. LDPE was fed into barrel 1 at a rate of 60lbs / h via a K-Tron KQX gravimetric feeder. A 1:1 solution of free radical generator and mineral oil was injected into barrel 9 via a 1000D ISCO syringe pump and a back pressure syringe valve to give a target concentration of 1000ppmw of active free radical generator. The polymer melt was then fed through a transition piece, a polymer diverter valve, and into an underwater 2-hole, 0.110 diameter die to produce pellets of about 37 counts / g.

[0123] Multilayer film

[0124] Example 1: A five-layer film was coextruded on a Reifenhauser extruder at a blow-up ratio (BUR) of 2.5, a temperature range of 185°C to 200°C, a thickness of 32 μm and an output rate of about 450 kg / h. The film contained DOWLEX TMTG 2085B linear low density polyethylene, MB-1 masterbatch and MB901250BX processing aid from Ampacet. Each layer accounts for 20% of the film volume. The content of each layer is shown in Table 2.

[0125] Table 2

[0126]

[0127] Example 2: A three-layer film was coextruded using a Collin Medical Line extruder with an 80 mm die, a 1.8 mm die gap, a 2.5:1 BUR, a thickness of 100 μm, and an output rate of about 1.50 kg / h. The temperature in the die was 230° C. The film contained DOWLEX TM GM8051 linear low density polyethylene, MB-1 and MB901250BX processing aid from Ancolor. The content of each layer is shown in Table 3.

[0128] Example 3: A three-layer film was coextruded with a higher level of MB-1 masterbatch as described in Example 2. The content of each layer is shown in Table 3.

[0129] Table 3

[0130]

[0131] Comparative Example 1: A five-layer film was coextruded as described in Example 1, except that instead of the MB-1 masterbatch, the film contained EB853 / 72 LDPE polymer (commercially available from Braskem) in the proportions shown in Table 4.

[0132] Table 4

[0133]

[0134] Comparative Example 2: A three-layer film was coextruded as described in Example 2, except that the MB-1 masterbatch was not used and the die temperature was 235° C. The proportions of the components are shown in Table 5.

[0135] Table 5

[0136]

[0137] test

[0138] The mechanical properties of the five-layer film from Example 1 and the five-layer film from Comparative Example 1 were measured using the procedures in the Test Methods. The results are shown in Table 6.

[0139] Table 6

[0140]

[0141] The properties of the three-layer films and their compositions from Examples 2 and 3 and the three-layer film and their compositions from Comparative Example 2 were measured using the procedures in the Test Methods. The results are shown in Table 7.

[0142] Table 7

[0143]

[0144] A number of heat seals were made at elevated temperatures using the multilayer films made in Inventive Example 2, Inventive Example 3, and Comparative Example 2 and using the sealing procedure in ASTM F2029. The seals were allowed to cool for 40 hours and then tested for seal strength using the procedure in the test method. The results are shown in Tables 8 and Figure 1 (In Figure 1 ) The results show that the films of the present invention maintain a strong seal over a wide range of sealing temperatures, whereas the seal using the comparative example films is strong only in a narrow temperature range and the seal strength decreases when the temperature exceeds the optimal temperature.

[0145] Table 8

[0146]

[0147] The hot tack strength of the seals was tested at elevated temperatures using the multilayer films made in Inventive Example 2, Inventive Example 3, and Comparative Example 2 and using the hot tack test listed in the Test Methods. The results are shown in Tables 9 and Figure 2 (In Figure 2 In the present invention, the second embodiment of the present invention is referred to as "the present invention 2.1", and the third embodiment of the present invention is referred to as "the present invention 2.2". )

[0148] Table 9

[0149]

Claims

1. A multilayer film comprising: (a) a main layer comprising an extruded first LLDPE composition comprising at least 85 wt% of a first LLDPE polymer, wherein the extruded first LLDPE composition has (1) a complex viscosity ratio (η) of at least 1.7 for complex viscosities measured at 190° C. and at angular frequencies of 0.1 rad / s and 10 rad / s. 0.1 / η 10 ); and (2) a ratio of 2.9 to 4.0 (Mz Abs / Mw Abs );as well as; (b) A second layer comprising a polymer composition.

2. The multilayer film of claim 1, wherein the second layer comprises a heat seal polymer.

3. The multilayer film according to any one of claims 1 or 2, further comprising: (c) a third polymer layer, the third polymer layer being directly or indirectly adhered to the primary layer opposite the second layer.

4. The multilayer film of any one of claims 1 to 3, wherein the extruded first LLDPE composition has a complex viscosity ratio (η ) of at least 1.8 for complex viscosities measured at 190°C and angular frequencies of 0.1 rad / s and 10 rad / s. 0.1 / η 10 ).

5. The multilayer film of any one of claims 1 to 3, wherein the extruded first LLDPE composition has a complex viscosity ratio (η ) of at least 1.9 for complex viscosities measured at 190°C and angular frequencies of 0.1 rad / s and 10 rad / s. 0.1 / η 10 ).

6. The multilayer film of any one of claims 1 to 5, wherein the extruded first LLDPE composition has a complex viscosity ratio (η t / s) of at least 8000 Pa-s for a complex viscosity measured at 190°C and an angular frequency of 0.1 rad / s. 0.1 ).

7. The multilayer film of any one of claims 1 to 5, wherein the extruded first LLDPE composition has a complex viscosity ratio (η t) of at least 9000 Pa-s for a complex viscosity measured at 190°C and an angular frequency of 0.1 rad / s. 0.1 ).

8. The multilayer film of any one of claims 1 to 7, wherein the extruded first LLDPE composition has a complex viscosity ratio (η t) of at most 5000 Pa-s for the complex viscosity measured at 190°C and an angular frequency of 10 rad / s. 10 ).

9. The multilayer film of any one of claims 1 to 8, wherein the film has a puncture force of at least 1.60 N / μm film thickness as measured by ASTM D5748 at 250 mm / min.

10. The multilayer film of any one of claims 1 to 9, wherein the film has a dart impact resistance of at least 6 g / μm film thickness as measured by ASTM D17-9 - Method A.

11. A method for producing a multilayer film according to any one of claims 1 to 10, the method comprising the following steps: (1) melting (a) a first LLDPE composition and (b) a polymer composition in separate extruders; and (2) coextruding the first LLDPE composition and the polymer composition under conditions suitable for forming a multilayer film comprising a main layer comprising the first LLDPE composition derived from the extrusion of the first LLDPE composition and a second layer comprising the polymer composition, and wherein: (a) prior to extrusion, the first LLDPE composition comprises (i) at least 85 wt% of a first LLDPE polymer, the first LLDPE polymer comprising at least 0.20 vinyl groups per 1000 carbon atoms; and (ii) 5 ppmw to 1000 ppmw of a free radical generator; and (b) the conditions in the extruder are adapted to substantially decompose the free radical generator.

12. The method of claim 11, wherein the free radical generator is a cyclic peroxide.

13. The method according to any one of claims 11 or 12, wherein: Prior to extrusion, the first LLDPE composition comprises from 10 ppmw to 100 ppmw of a free radical generator.

14. The method according to any one of claims 11 to 13, wherein: Prior to extrusion, the first LLDPE composition comprises (1) a first LLDPE polymer and (2) a masterbatch containing a carrier polymer and 10 ppmw to 1000 ppmw of the free radical generator, wherein the carrier polymer is a LLDPE polymer or a LDPE polymer.

15. The method of any one of claims 11 to 14, wherein the extruded first LLDPE composition in the multilayer film has a complex viscosity ratio (η) at least 10% higher than the complex viscosity ratio of the first LLDPE polymer before extrusion. 0.1 / η 10 ).

Citation Information

Patent Citations

  • Collation shrink films

    EP2653392A1

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Process for the polymerization of ethylene

    US4352915A